Interpretasi Al Quran Menurut Pemikiran Abdullah Saeed untuk Pengembangan Ekonomi Syariah - Fatma Wati Sungkawaningrum (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2020)
Human thought everywhere is preoccupied with what he has seen before. Emerged into an idea that is later expected to be a guideline or even an order of values ​​that applies to a human civilization. As a blessed people, the heart, the mind, and the power of reason, give the signal that the matter is not necessarily true and especially if it will be standardized. With research metode sociology in this life, we are also required to be open-minded and not dogmatic and rigid. That religious and pluralistic life, makes us in interpreting a sentence can be based on a value order that applies in a country. When interpreting remains based on the framework of aqeedah as taught by the Prophet Muhammad SAW, such as in life in a country. When a woman travels alone at night or drives a car alone, then this matter is not the same interpretation between one country and another. In our country it is not a problem but it can be a ban if in other countries. In economics will also certainly find a similar subject, and in the study and application of technology we also can not avoid or reject the speed of technology. We are required to be able to manage and deal with it, and manage it. Muslims are still required to compete in this global world so that we not only become spectators or mere supporters, but also must strive to appear as actors in the sense that we can place ourselves in every value order without denying Islamic beliefs